Absorption cross sections in the CH stretching region for propene broadened by helium and nitrogen. (September 2021) - Dodangodage, Randika; Bernath, Peter F.; Zhao, Jianbao; Billinghurst, Brant
Highlights: High resolution Fourier transform spectroscopy of propene at 202–295 K. Infrared absorption cross sections of propene for 2680–3220 cm −1 region. Helium and nitrogen used as broadening gases. Data are useful for planetary atmospheres including giant planets and Titan. Abstract: Propene infrared absorption cross-sections are important for quantitative analysis of atmospheric spectra. Propene has been observed in Titan's atmosphere and may be detected in the atmospheres of giant planets. Infrared absorption cross-sections of propene (C3 H6 ) have been measured in the 2680–3220 cm −1 region by high-resolution Fourier transform spectroscopy. Samples of propene were held at 202, 232, 265, 295 K with helium and nitrogen broadening gas pressures of 10, 30, 100 Torr. The cross section files are available for download.